2020
DOI: 10.3390/su12124853
|View full text |Cite
|
Sign up to set email alerts
|

Financial Sustainability of Selected Rain Water Harvesting Systems for Single-Family House under Conditions of Eastern Poland

Abstract: Recent climate changes limiting the available water resources require careful sustainable water management in the cities, the locations of highest drinking water consumption and sanitary sewage and stormwater generation. Over 50% of water demand in the residential areas of cities cover activities in which non-potable water could be used, e.g., toilets and laundry facilities, cleaning, garden irrigation and washing vehicles. Thus, rain water harvesting (RWH) systems are the sustainable alternative water supply,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…The profitable investment is characterized by the value of BCR indicator higher than 1 (BCR ≥ 1). BCR can be calculated from the following equation [31]:…”
Section: Methods For Economic Criterion Assessmentmentioning
confidence: 99%
“…The profitable investment is characterized by the value of BCR indicator higher than 1 (BCR ≥ 1). BCR can be calculated from the following equation [31]:…”
Section: Methods For Economic Criterion Assessmentmentioning
confidence: 99%
“…Stormwater fees are common in the U.S. and Canada, as shown by the latest survey from 2021 [55]. Research on stormwater fees has been the subject of many analyses of their impact on the development of green infrastructure, which proved their effectiveness; for example: (1) the assessment of stormwater fees in Germany (also noted as imperviousness fees) [56][57][58] showed a 10% decrease in the impervious area in Munich [56]; (2) Qiao et al, in two research papers [17,45], analyzed the governance factors of sustainable stormwater management and recommended the use of stormwater fees as an important incentive; and (3) analyses of stormwater fees in Poland were conducted in terms of their impact on the economic efficiency of green infrastructure [59][60][61], and they were also mentioned as important factors in the development of sustainable stormwater management [62,63]. Thurston et al analyzed auctions and fees as incentive methods, and concluded that relatively minimal financial incentives could encourage homeowners to retain stormwater runoff on their property [47].…”
Section: Introductionmentioning
confidence: 99%
“…One of the strong grounds behind it might be the investment cost [1]. This issue is considered as an important obstacle for most nations to the extent that many leading experts and researchers are of the belief that there is a strong link between sustainability of the RHSs and financial aspects of their construction [15,16]. The study of economic aspect of the RHSs by Dijk et al [17] indicated that strategically designed, financed, and implemented rooftop RHSs meet large-scale urban water infrastructure needs.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this fact, modelling and numerical calculations could address the associated issues. The economical sustainability of the RHSs designs for assessment of the affordability and profitability of the investment in the RHSs was studied by Musz-Pomorska et al [15] in Poland. In this survey the significance of the governmental financial support and restricted profitability of the RHSs were revealed.…”
Section: Introductionmentioning
confidence: 99%